Morphological adaptability of graphitic carbon nanofibers to enhance sodium insertion in a diglyme-based electrolyte. Issue 16 (4th April 2019) - Nacimiento, Francisco; Cabello, Marta; Ortiz, Gregorio F.; Alcántara, Ricardo; Lavela, Pedro; Tirado, José L.
Abstract : A novel sodium insertion mechanism by an activation process that enhances its accessibility to redox centres at the interlayer space. Abstract : The recent introduction of glyme-based solvents has opened new opportunities to characterize graphitic materials as anodes for sodium-ion batteries. We evaluated the electrochemical behaviour of a graphitized carbon nanofiber for the first time. X-ray diffraction, electron paramagnetic resonance and nuclear magnetic resonance allowed the sodium insertion mechanism to be untangled, in which the occurrence of an activation process during the first discharge enhances sodium accessibility to active redox centres at the interlayer space. Morphological changes observed by electron microscopy could be responsible for this behaviour. A fully graphitized carbon nanofibers/NaPF6 (diglyme)/Na3 V2 (PO4 )3 sodium-ion battery was tested to probe the reliability of this graphitic nanostructure as a negative electrode.